Hot corrosion of arc ion plating NiCrAlY and sputtered nanocrystalline coatings on a nickel-based single-crystal superalloy. (15th July 2017) - Wang, Jinlong; Chen, Minghui; Cheng, Yuxian; Yang, Lanlan; Bao, Zebin; Liu, Li; Zhu, Shenglong; Wang, Fuhui
Highlights: Hot corrosion of three metallic coatings was investigated. NiCrAlY coating loses protectiveness against hot corrosion due to scale spallation. The two nanocrystalline coatings perform better than NiCrAlY in hot corrosion. Ta oxidation leads to scale pitting and corrosion of the nanocrystalline coating. Y addition in the nanocrystalline coating reduces such harmful effect of Ta. Abstract: Hot corrosion in sulfate salt at 850 °C of three metallic coatings is investigated comparatively. The NiCrAlY coating loses its protectiveness after 200 h corrosion. Its oxide scale spalls off partly and becomes porous as a consequence of basic fluxing. The nanocrystalline coating (SN) performs better than the NiCrAlY one, but its scale is porous as well. Oxidation and/or sulfidation of Ta account for the formation of pores. The yttrium modified nanocrystalline coating (SNY) provides the highest corrosion resistance. Yttrium completely inhibits oxidation and sulfidation of Ta. Its scale is intact and adherent, and exclusively composted of alumina.